Revolutionizing Dance: Advanced Choreographic Trends of the 21st Century - Chandnasaro, Dharakorn (Journal of Urban Culture Research, 2025)
The study, "Revolutionizing Dance: Advanced Choreographic Trends of the 21st Century," provides an in-depth examination of the contemporary dance landscape. This paper underscores the significance of emerging dance paradigms in the 21st century, artfully blending time-honoured traditions with cutting-edge innovations, promoting artistic ingenuity, stringent discipline, and synergistic collaborations. Central principles highlighted include interdisciplinary partnerships and a heightened awareness of environmental issues, both of which contribute substantially to the broader dance discourse. Additionally, the work accentuates the essentiality of copyright awareness and the diligent deterrence of dance plagiarism, pivotal in safeguarding choreographers' rights and advocating for an ethos underscored by respect and ethical integrity. This scholarly contribution delivers valuable perspectives for professionals, educators, and enthusiasts, deepening comprehension of the dynamic shifts characterizing 21st century dance.